The punctuality of the airline in air transportation system: Factors of flight delay in-time - Goh, Phoey Keng; Sabar, Rohafiz (2012)
The research purpose is to evaluate the relationship between on-time flight performances with the factor of the flight delay in-time.Departure and arrival punctuality is the key performance indicators of airlines and essentials for time valuing travelers.A crucial driver for good punctuality is good planning.Potential reasons of delays maybe weak in planning such as lack of communication, inefficiency of the ground operational factor, airport congestion problem, and other unexpected condition such as weather condition. Secondary data of the methodology will be useful for the research paper.